Gang in translation: Official and vernacular representations of a "Roma" drug gang in Czechia - Kupka, Petr (Crime, media, culture, 2022)
This study focuses on the social construction of gangs in Czechia. Although the country is not usually associated with the activities of street gangs, the adoption of gang representations is evident in this context, including the use of the gang label itself. In order to capture the gang glocalization process, I employ the concept of translation, whereby glocalization is conceptualized as a complex process of the transposition of symbols based on the constant assessment and negotiation of the formed equivalent in the new discursive context. This approach allows us to understand the similarities and differences between how gangs are labelled not only across various cultural contexts, but also within them, with a honed analytical focus on the discursive strategies of the actors being studied. The concept of glocalization as translation is illustrated using the example of the Novák collective operating in a marginalized urban area in Czechia. While official discourse characterized this collective as an international drug gang, this construction was entirely absent in the discourse employed by the residents of the area. This discrepancy explains the gang construct within Czech public discourse as an equivalent of organized and sophisticated crime which automatically excludes certain ethnic groups by definition.